Transarterial chemoembolization combined with lenvatinib plus tislelizumab for unresectable hepatocellular carcinoma: a multicenter cohort study - Zhao, Yushan; Wen, Shuwei; Xue, YaoQing; Dang, Zhijun; Nan, ZhiYu; Wang, Dong; Li, Xiao; Feng, Duiping; Chen, Yi (Frontiers in Immunology, 2024)
Objective Comparing the efficacy of transarterial chemoembolization (TACE) combined with lenvatinib plus tislelizumab (TLT) with TACE combined with lenvatinib (TL) for unresectable hepatocellular carcinoma, particularly in determining which patients can benefit more from the TLT treatment. Methods From March 2021 to September 2023, a total of 169 patients from three centers were included in this study, with 103 patients receiving TLT and 66 patients receiving TL. The Kaplan-Meier method was utilized to evaluate the cumulative overall survival (OS) and progression-free survival (PFS) between the two groups and were assessed using the log-rank test. Subgroup analysis on tumor number, maximum tumor diameter, presence of portal vein thrombosis, AFP level, and Child-Pugh class were conducted. Results The median OS was 26 months in the TLT group, and 20 months in the TL group. The median PFS was 14 months in the TLT group and 9 months in the TL group. The Kaplan-Meier curve demonstrated a significantly superior OS and PFS in the TLT group compared to the TL group. Subgroup analysis showed that for patients with a maximum tumor diameter greater than 7 cm, AFP > 400 ng/ml and accompanied by portal vein tumor thrombus, and Child-Pugh class A, there was a statistically significant difference in OS between TLT and TL groups. Conclusions OS and PFS were significantly improved in patients who received TLT compared to those who received TL, patients with a largest tumor diameter greater than 7 cm, AFP > 400 ng/ml, Child-Pugh class A and PVTT appeared to derive more benefit.